A dignidade da pessoa humana como condicionante à presunção de veracidade dos atos administrativos - Santos, Luiz Antônio de Alcântara (2024)
The present paper will consist of analyzing the presumption of truthfulness of administrative acts in the Democratic State of Law, in light of the Principle of Human Dignity, considering the repercussions of this as an axiological core of the Brazilian legal system. In addition to the necessary investigation of the historical and philosophical aspects that led to the foundations of the supremacy of the public interest and the presumption of legitimacy attributed to the acts of the administrative entity (the State), the research will explore the tendency to optimize the norms of fundamental rights, imposed for the values enshrined in the Brazilian Constitution of 1988, and the implications of the right to due legal process in a state that presupposes democracy and the Rule of Law. The achievement of these objectives will make use of the deductive method for the analysis and dissection of the concepts and legal norms that involve the topic, which will allow measuring the implication of each norm in the Brazilian legal system. Furthermore, the inductive method will serve to identify whether there is a collision between the public interest that supports the application of the presumption of truthfulness in the Democratic Rule of Law and the preservation of rights inherent to the Dignity of the Human Person, as well as the treatment conferred by the Law to such a shock. The methodology will also use the list of necessary concepts, as well as the definition of the contours of the possible collision indicated, proceeding to the discussion of the content produced through the dialectical method, in order to achieve the objectives of the paper. In the search for identifying what would be the conditions that the application of the presumption of truthfulness would need to have to guarantee respect for the Dignity of the Human Person and the rights projected by it, the paper aims to suggest guidelines that could contribute to the harmonious coexistence of this traditional prerogative of the Public Administration with fundamental rights in the current Brazilian political-legal regime.